A Study on Private Sector Banks and Marketing of Financial Services: Exploring Customer Interactions in Private Sector Banks (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A service can be describedas the way in which we deal with our customer each time they have a ‘serviceencounter’. This encounter is the direct interaction between the organizationand one of its customers and can occur in one of many ways. For example, a bankcustomer who wishes to draw money from his account can do so in one of manyways. He can go to a branch and request the money from a cashier, he can gointo the branch and use an ATM, or he can use an ATM situated in a remotelocation away from the branch of the bank. Each of these is an interaction withthe organization, and the way in which the customer is dealt with during thatinteraction is important to the customer and the way he or she feels about theservice.